2021
DOI: 10.1029/2020gl089962
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Temporal Variability in Wave‐Particle Interactions in Earth's Radiation Belts

Abstract: Physics-based radiation belt models of electron behavior often focus on the wave-particle interactions that accelerate and scatter particles or contribute to radial diffusion. These models make considerable use of quasilinear theory to describe the wave-particle interactions (e.g., Lyons et al., 1972; Ripoll et al., 2020) and can be used to study the flux of high-energy electrons on a range of time scales, from single storms (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(43 citation statements)
references
References 30 publications
(55 reference statements)
2
41
0
Order By: Relevance
“…This suggests that when constructing a drift-average, an average of observation-specific bounce-averaged coefficients is likely to work well, since the effective timescales for electrons drifting through chorus wave regions are very short. Further numerical experiments, similar to those in Watt et al (2021), but using an appropriate distribution of chorus diffusion coefficients constructed as in Watt et al (2019) should confirm whether the timescales indicated in Figure 7c are short enough to allow for straightforward averaging.…”
Section: Temporal Scale Size Of Chorus Wavesmentioning
confidence: 83%
See 4 more Smart Citations
“…This suggests that when constructing a drift-average, an average of observation-specific bounce-averaged coefficients is likely to work well, since the effective timescales for electrons drifting through chorus wave regions are very short. Further numerical experiments, similar to those in Watt et al (2021), but using an appropriate distribution of chorus diffusion coefficients constructed as in Watt et al (2019) should confirm whether the timescales indicated in Figure 7c are short enough to allow for straightforward averaging.…”
Section: Temporal Scale Size Of Chorus Wavesmentioning
confidence: 83%
“…The temporal scale size of chorus waves has not been studied statistically and quantitatively before. Recent numerical experiments demonstrate that, the temporal variability is very important for diffusion models due to the wave‐particle interactions (Thompson et al., 2020; Watt et al., 2019, 2021). Figures 5a–5d show the temporal correlations are proportional to time lag ( e −0.0067 *Δ t ) and drops to 0.5 when Δ t = 10 s, which means the statistically temporal scale size of chorus wave only lasts ∼10 s, and could be negligible compared to the electron diffusion timescales.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations